THU0180 Identifying rapid radiographic progressors in rheumatoid arthritis. (1st June 2001) - Wong, JB; Wong, CJ; Van Riel, PL; Hazes, JM; Breedveld, FC; Van der Heijde, DM; Feagan, BG
Abstract : Background: Mounting evidence suggests that radiographically progressive disease identifies rheumatoid arthritis patients at higher risk for developing future disability. Hand and foot radiographs, however, incur additional expense and have not become a part of routine practice. Objectives: To determine if clinical parameters can be used to identify patients with radiographic progression. Methods: In 2 Dutch cohorts of early rheumatoid arthritis patients from Leiden and Nijmegen, 279 patients had year 2 or 3 radiographs (mean age 50.5 years, 76.7% women, 71.7% RF+, 60.1% HLA DR4+). Using the OMERACT definition, radiographic progression was defined as exceeding the smallest detectable difference (SDD) or 15 modified Sharp units. Because x-rays were done after 2 or 3 years from RA onset, we used the annual radiographic progression rate to define progressors (>7.5) vs non-progressors ( Results: In this cohort, 199 of the 279 patients (71%) were radiographic ?progressors? after 2 – 3 years of RA. Univariate analysis showed that older age, RF+, higher Disease Activity Score (DAS) and Ritchie articular index (all p < 0.03) were associated with radiographic progression. In the multivariate model, RF positivity (OR 4.78, CI 2.32 – 9.86), older age (OR 1.75 per 10 years, CI 1.36 – 2.27) and higher DAS (OR 1.88, CI 1.32 – 2.69) remained significant. The area under the ROC was 0.81. The resulting sensitivity (SEN) and specificity (SP) values using the following cutpoints were (cutpoint = SEN/SP): 0.50 = 94/48, 0.60 = 89/60, 0.70 = 81/68, 0.80 = 64/79. Thus, treating all patients with predicted probabilities above 0.50 would miss 6% of the radiologic progressors and result in treatment of 52% of the non-progressors. Or treating only patients with predicted probabilities above 0.80 would miss 36% of the progressors and treat 21% of the non-progressors. Conclusion: Non-radiographic clinical parameters do not adequately identify rheumatoid arthritis patients with radiographically progressive joint disease. Performing routine x-rays to target new RA treatments that stabilise radiologic joint disease toward radiologic progressors is likely to yield the most favourable cost-effectiveness ratios.